Carotid Arterial Stiffness and Risk of Incident Cerebral Microbleeds in Older People. Issue 8 (August 2015) - Ding, Jie; Mitchell, Gary F.; Bots, Michiel L.; Sigurdsson, Sigurdur; Harris, Tamara B.; Garcia, Melissa; Eiriksdottir, Gudny; van Buchem, Mark A.; Gudnason, Vilmundur; Launer, Lenore J.
<x xml:space="preserve">Abstract</x> Objective— Age and high blood pressure are major risk factors for cerebral microbleeds (CMBs). However, the underlying mechanisms remain unclear and arterial stiffness may be important. We investigated whether carotid arterial stiffness is associated with incidence and location of CMBs. Approach and Results— In the prospective, population-based Age, Gene/Environment Susceptibility (AGES)-Reykjavik study, 2512 participants aged 66 to 93 years underwent a baseline brain MRI examination and carotid ultrasound in 2002 to 2006 and returned for a repeat brain MRI in 2007 to 2011. Common carotid arterial stiffness was assessed using a standardized protocol and expressed as carotid arterial strain, distensibility coefficient, and Young elastic modulus. Modified Poisson regression was applied to relate carotid arterial stiffness parameters to CMB incidence. During a mean follow-up of 5.2 years, 463 people (18.4%) developed new CMBs, of whom 292 had CMBs restricted to lobar regions and 171 had CMBs in a deep or infratentorial region. After adjusting for age, sex, and follow-up interval, arterial stiffness measures were associated with incident CMBs (risk ratio per SD decrease in carotid arterial strain, 1.11 [95% confidence interval, 1.01–1.21]; per SD decrease in natural log-transformed distensibility coefficient, 1.14 [1.05–1.24]; and per SD increase in natural log-transformed Young elastic modulus, 1.13 [1.04–1.23]). These measures were also significantly associated with incident deep CMBs (1.18 [1.02–1.37]; 1.24 [1.08–1.42]; and 1.23 [1.07–1.42]) but not with lobar CMBs. When further adjusted for blood pressure and other baseline vascular risk factors, carotid plaque, prevalent CMBs, subcortical infarcts, and white matter hyperintensities, the associations persisted. Conclusions— Our findings support the hypothesis that localized increases in carotid arterial stiffness may contribute to the development of CMBs, especially in a deep location attributable to hypertension.